Immigration, screening, and cervical cancer incidence: an application of Age–Period–Cohort analysis. Issue 6 (November 2019) - Bucchi, Dania; Chiavarini, Manuela; Bianconi, Fortunato; Galeotti, Maria E.; Gili, Alessio; Stracci, Fabrizio
Abstract : Cervical cancer (CC) control is based on the implementation of effective screening programs. In the coming years, human papilloma virus vaccination coverage will contribute considerably toward cancer prevention. In Italy, where an organized screening program has been implemented, immigration from low/middle-income countries with a high prevalence of human papilloma virus infections has increased steadily over the last decades. To assess the impact of screening efforts in counteracting background changes, we analyzed the incidence trends of cervical intraepithelial neoplasia grade 3 carcinomas in situ (CIS) and invasive CC from 1994 to 2013 through an Age–Period–Cohort model using data of a regional population-based registry. Moreover, using Joinpoint regression, we compared the incidence of cervical lesions in native women with that observed in foreign-born women, highlighting the differences in age and screening status. The results indicate that the CC incidence trend decreased in Italian women (annual percent change = −2.7*%, 95% confidence interval = −4.3; −1.1), but increased (APC = 12.2*%, 95% confidence interval = 7.6; 17.0) in immigrants. For CIS, incidence rates show a growing trend in both groups, especially in women born abroad. For cancer, no marked changes in period-specific incidence rate ratios were detected until around 2000, when we found a slight decrease, followed by an increase. For CIS, we estimate an important upward trend in cohort-specific risks. The favorable effect of screening in preventing an increase in CC incidence has been counteracted by the progressive increase in immigrants from high-risk countries, where it is of increasing relevance to extend the use of vaccination.